Nutrición y su incidencia en el desarrollo psicomotriz de los niños y niñas del nivel inicial de la escuela fiscal mixta “13 de Julio”, de la ciudad de Paccha, cantón Atahualpa, provincia de El Oro, período lectivo 2014-2015” lineamientos alternativos - Añazco Añazco, Paola Katherine (2016)
This RESEARCH titled: NUTRITION AND ITS IMPACT ON THE PSYCHOMOTOR DEVELOPMENT OF CHILDREN FROM PRESCHOOL OF “13 DE JULIO” SCHOOL IN THE CITY OF PACCHA, ATHAHUALPA CANTON, EL ORO PROVINCE, DURING THE SCHOOL YEAR 2014-2015. ALTERNATIVE GUIDELINES. The main problem of this research is: lack of appropiate nutrition in children from the evaluated school, this leads us to ask the following question. How does nutrition affect the psychomotor development of the children from “13 of July” public school? The overall objective of this research is to determine Nutrition and Its Impact on the Psychomotor Development of children from preschool of “13 of July” school in the city of Paccha, Atahualpa canton, El Oro province, during the school year 2014 – 2015. The main methods used in this research are: scientific, inductive, deductive and statistics. Besides, another instruments and techniques were used, such us surveys to the parents, in order to define the type of daily food their children have; and Dexterimetro De Gooddard Test applied to the children FROM PRESCHOOL OF “13 DE JULIO” SCHOOL to value Their PSYCHOMOTOR DEVELOPMENT. Through these resources we gathered accurate information to fulfill our research. In the results of this study, 100% of parents surveyed believe that nutrition in an adequately quantity and quality helps children to have a good psychomotor development, being the basis for their performance in different physical and intellectual activities. According to the results of Dexterimetro De Gooddard Test, the level of psychomotor development was assessed in children; with the following percentages 9% of children achieved a higher level of psychomotor development; very good 11%; good 26%; Regular 17%; 14% poor; and 23% very poor, so it is possible to determine that there is a very low level of psychomotor development which requires greater stimulation in this area.